EFFECT OF INTERNET BANKING ON GROWTH OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of the Management Sciences, 2023)
This study assesses the effect of WebPay and Point of sale (POS) Terminal on the total deposits of deposit money banks in Nigeria. The Data for the study was sourced through secondary data source obtained from Central Bank of Nigeria Statistical Bulletin from 2009 to 2021. The time series data were analyzed using Ordinary least square econometric techniques. The study reveals that the use of WebPay has a negative insignificant effect on the total deposits of deposit money banks in Nigerian while  the use of POS terminals has a negative Significant effect on the total deposits of deposit money banks in Nigeria for the periods under study. The study concludes that the use of Webpay and POS  electronic payment systems has varying negative effects on total deposits of banks. The study therefore recommend deposit money bank should identify ways to increase its usage and should consider re-evaluating their POS terminal usage by identifying ways to mitigate the negative impact.
Keywords: Internet; banking; Webpay; deposit; pos